Lung cancer eight years after radioactive seed migration. (2016) - Lin, Angela; Sun, Alexander; Bezjak, Andrea; Bissonnette, Jean-Pierre; Tanguay, Jeffrey; Keshavjee, Shaf; Saibishkumar, Elantholi P.
Abstract: We report here an occurrence of non-small cell lung cancer in a patient who had pulmonary radioactive seed emboli from his prostate brachytherapy 8 years post procedure. The potential etiological role of radiation carcinogenesis should be recognized.